2018
DOI: 10.1123/jsep.2017-0318
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Parents’ Coping Strategies on the Relationship Between Parents’ Emotional Intelligence and Sideline Verbal Behaviors in Youth Soccer

Abstract: The overall purpose of this study was to examine the mediating effects of parents' coping strategies on the relationship between parents' emotional intelligence and sideline verbal behaviors during their children's soccer games. Participants were 232 parents (120 mothers and 110 fathers) of youth soccer players age 9-13 years. Observations in situ were carried out at 30 soccer games during a soccer tournament. At the end of the game, parents were approached and asked to complete the Emotional Intelligence Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
2
18
0
2
Order By: Relevance
“…In serial mediation models, the bright side motivational model presented a full mediation (β = 0.45 [0. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]; P M = 0.90), which reinforces this study's previous findings regarding similar model testing and mediators' influence on persistence. In this model, only the enjoyment mediator presented significant positive indirect effects on persistence (β = 0.30 [0.22-0.39]).…”
Section: T a B L E 4 Path Estimates Indirectsupporting
confidence: 85%
See 1 more Smart Citation
“…In serial mediation models, the bright side motivational model presented a full mediation (β = 0.45 [0. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]; P M = 0.90), which reinforces this study's previous findings regarding similar model testing and mediators' influence on persistence. In this model, only the enjoyment mediator presented significant positive indirect effects on persistence (β = 0.30 [0.22-0.39]).…”
Section: T a B L E 4 Path Estimates Indirectsupporting
confidence: 85%
“…As a complementary sample size analysis, G*Power v3.1 software was used to calculate the minimum required sample size. Past studies have used this program as a way of determining sample size when the number of participants did not adhere to the recommended 10:1 ratio or the minimum 5:1 ratio. Thus, as a complementary analysis, G*Power 3.1 was used to calculate the required sample size, including the following parameters: anticipated effect size of f 2 = 0.01, α = 0.05, and statistical power = 0.95, suggesting a minimum of 287 participants, which was respected in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It would be interesting to extend this study to other cultures that are likely to regulate emotions and express different coach behaviors in competitive settings. Third, from a measurement point of view, although WLEIS (Wong and Law, 2002) have presented once again good psychometric characteristics in sport (e.g., Lee and Chelladurai, 2016; Teques et al, 2018), more research is needed to develop and validate a sport-specific self-report EI ability measure. This would involve the steps commonly used to create a sport-specific scale in sport settings and an in-depth examination of the relationships between the measure and other established constructs associated with EI, such as personality or achievement motivation (Mayer et al, 2008), to clarify any redundancies often associated with EI trait approach (e.g., Joseph and Newman, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have focused on the relationship among athletes’ EI and psychosocial and behavioral correlates, including relationships with individual athletic performance (e.g., Zizzi et al, 2003; Laborde et al, 2014a), pleasant emotions that athletes experience on the day of competition, such as happiness, vigor and calmness (e.g., Lane and Wilson, 2011), use of psychological skills during and outside competitions (e.g., Lane et al, 2009), physiological responses (e.g., Laborde et al, 2011), cooperative behaviors in highly competitive conditions (Perry and Clough, 2017), and organizational functioning (e.g., Wagstaff et al, 2013). Recently, evidence showed that EI appears to play an important role in regulating parents’ sideline verbal behaviors during youth soccer games (Teques et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…No desporto, a regulação emocional parece influenciar os comportamentos em competição (e.g., Teques, Calmeiro, Martins, Duarte, & Holt, 2018). No alto rendimento desportivo, as exigências e o sentimento de competência são cada vez maiores, e é aqui que a psicologia do desporto se encarrega de analisar, estudar e observar as condutas, reações e respostas emocionais do indivíduo (Martínez, Moya-Faz & Ruiz, 2013).…”
Section: Introductionunclassified